View Single Post
Old 02-09-2004, 12:26 PM   #7 (permalink)
KnifeMissile
 
KnifeMissile's Avatar
 
Location: Waterloo, Ontario
Okay, fine. Since so many people were so interested in this problem, I'll just post the solution right here!

You want to add the identity, 0, but in a very convenient form.

Let S be the summation symbol, represented in this clumsy ASCII form like so:

S(i=0,k)(a^i) = a^0 + a^1 + ... + a^k

So, add the identity 0 = S(i=1,n-1)(a^i) - S(i=1,n-1)(a^i) and the formula will simplify right before your eyes!

Code:
a^n - 1 = a^n - 1 + 0
        = a^n - 1 + S(i=1,n-1)(a^i) - S(i=1,n-1)(a^i)
        = S(i=1,n-1)(a^i) + a^n - 1 - S(i=1,n-1)(a^i)
        = a( S(i=0,n-2)(a^i) + a^(n-1)) - S(i=0,n-1)(a^i)
        = a*S(i=0,n-1)(a^i) - S(i=0,n-1)(a^i)
        = ( S(i=0,n-1)(a^i) ) * (a - 1)
As you can see, a^n -1 can be decomposed into two factors, S(i=0,n-1)(a^i) and a - 1. But a - 1 is supposed to be prime, so the only way that these two terms can not be factors is if a - 1 = 1.

Therefore, a = 2.
QED.


Pretty cool, eh!
KnifeMissile is offline  
 

1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73